Urgensi Tanggung Jawab Pendidikan Kejiwaan pada Anak Usia Sekolah Dasar dalam Perspektif Pendidikan Holistik - Eko Kurniawanto (Jurnal Pendidikan Dirgantara, 2025)
This research highlights the importance of the responsibility of mental education for elementary school-aged children from a holistic education perspective. The main objective of this study is to emphasize the need for a comprehensive approach to children's education, which not only focuses on academic aspects but also on emotional and psychological development. Holistic education views the child as a whole, encompassing physical, cognitive, social, and emotional development, all of which are crucial in shaping character and mental health. This study underscores that elementary education should create an environment that supports the psychological development of children, enabling them to grow into balanced individuals, capable of handling emotional challenges, and mentally prepared to face life's difficulties. The research also discusses the role of educators, parents, and the community in supporting children's mental education, as well as the urgency of integrating psychological aspects into the elementary school curriculum. Therefore, this study advocates for reforms in educational approaches to create a generation that is mentally healthy, well-balanced, and ready to contribute positively to society.